Development of a high-yield live-virus vaccine production platform using a novel fixed-bed bioreactor. Issue 20 (29th April 2020) - Berrie, Dalton M.; Waters, Robin C.; Montoya, Christopher; Chatel, Alex; Vela, Eric M.
Abstract: The increasing importance of viral vaccine manufacturing has driven the need for high cell density process optimization that allows for higher production levels. Vero cells are one of the more popular adherent cell lines used for viral vaccine production. However, production is limited due to the logistical limitations surrounding adherent cell line processes, such as large equipment footprints, time and labor-intensive processes, and larger costs per dose. We have addressed this limitation with the establishment of a viral vaccine production system utilizing the novel single use scale-X™ carbo bioreactor. The unit is compact and is scalable and one of the novel features of the system is the continuous in-line downstream purification and concentration processes associated with the bioreactor vessel. We present the results from a campaign featuring a proprietary Vero cell line for production of a live recombinant Vesicular stomatitis virus vaccine that features the Lassa Fever virus glycoproteins. Metabolite analyses and viral yield comparison between traditional flasks, cell factories, and the scale-X carbo bioreactor were performed, and on average, the single use bioreactor produced 2–4 logs higher titers per surface area, approximately 5 × 10 10 pfu/cm 2, compared to classical flatstock, 2.67 × 10 6 pfu/cm 2, and cell factories production, 5.77 × 10 8 pfu/cm 2 . Overall, we describe a novel bioreactor platform that allows for a cost-efficient and scalable process for viral vaccine production.